2022
DOI: 10.3390/md20110707
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Extract of Marine Algae, Halymenia durvillei, Provides Photoprotection against UV-Exposure in L929 and HaCaT Cells

Abstract: Halymenia durvillei is a red alga distributed along the coasts of Southeast Asian countries including Thailand. Previous studies have shown that an ethyl acetate fraction of H. durvillei (HDEA), containing major compounds including n-hexadecanoic acid, 2-butyl-5-hexyloctahydro-1H-indene, 3-(hydroxyacetyl) indole and indole-3-carboxylic acid, possesses high antioxidant and anti-lung cancer activities. The present study demonstrated that HDEA could protect mouse skin fibroblasts (L929) and human immortalized ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The skin ECM is composed mainly of elastic fibers and collagen, which play an important role in the skin tissue and cells by providing a structural framework. Studies have reported that skin sagging and coarse wrinkle formation occurs through ECM degradation by MMPs [ 6 , 7 , 22 ]. Notably, the expression of MMPs is induced by prolonged UV light exposure, which causes wrinkle formation due to the breakdown of ECM proteins and collagen [ 6 , 7 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The skin ECM is composed mainly of elastic fibers and collagen, which play an important role in the skin tissue and cells by providing a structural framework. Studies have reported that skin sagging and coarse wrinkle formation occurs through ECM degradation by MMPs [ 6 , 7 , 22 ]. Notably, the expression of MMPs is induced by prolonged UV light exposure, which causes wrinkle formation due to the breakdown of ECM proteins and collagen [ 6 , 7 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that skin sagging and coarse wrinkle formation occurs through ECM degradation by MMPs [ 6 , 7 , 22 ]. Notably, the expression of MMPs is induced by prolonged UV light exposure, which causes wrinkle formation due to the breakdown of ECM proteins and collagen [ 6 , 7 , 23 ]. Therefore, we propose that inhibition of MMP expression is a potential strategy to inhibit wrinkle formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the PA obtained from the methanolic extract of Syzygium litoralle (Myrtaceae) showed antioxidant activity, with an IC50 value of 44.85 µg/mL [53]. Consistently, PA-enriched Halymenia durvillei extract was able to reduce intracellular reactive oxygen species (ROS), as well as to increase the upregulation of mRNA transcripts of antioxidant enzymes in mouse skin fibroblasts (L929) and human immortalized keratinocytes (HaCaT) to promote photoaging activity [54]. Similarly, the present study demonstrates that high-glucose-fed worms treated with CLET, which contains a significant amount of PA, showed decreased intracellular ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Cell assays also focused on skin-related disorders, following consumers' rising aware of skin aging and search for ways to counteract this trend with novel active ingredients [79]. Besides exerting anti-inflammatory effects through the abovementioned general anti-inflammatory mechanisms, some macroalgal compounds additionally had a protective activity of the skin barrier [80], decreased wrinkle formation [81], increased cell proliferation and collagen production in human dermal fibroblasts [82], and downregulated the expression of MMPs [83], contributing to overall skin health. In vivo studies (Table 5) followed the same trend as cell experiments by mainly evaluating general inflammation (n = 7 for macroalgal and n = 2 for microalgal studies) and skin disorders (n = 2, 1 study for each algae type).…”
Section: Algal Applications In Managing Inflammatory Conditionsmentioning
confidence: 99%